2C.06: BLOOD PRESSURE CONTROL IN THE CONTEXT OF SCREENING FOR COGNITIVE AND MOOD IMPAIRMENTS IN THE OCTOGENARIAN AND OLDER HYPERTENSIVE PATIENTS. (June 2015) - Piotrowicz, K.; Prejbisz, A.; Klocek, M.; Topor-Madry, R.; Kawecka-Jaszcz, K.; Januszewicz, A.; Narkiewicz, K.; Grodzicki, T.; Gasowski, J.
Abstract : Objective: To assess blood pressure control rate and its correlates in a Polish nationwide cohort of the community dwelling persons at or above the age of 80 years. Design and method: As a part of PolFokus study we did a cross-sectional, nationwide survey of 2500 elderly people treated for hypertension for at least one year. In the current analysis we included data of 384 individuals aged 80+. During the survey visit BP was measured at least twice and the mean value was calculated. Demographic and medical data were collected. Adherence to antihypertensive medications was assessed, and screening tests for cognitive deficits (Abbreviated Mental Test Score, AMTS) and mood disorders (Geriatric Depression Scale, GDS) were performed. Logistic regression models were used to calculate the probability of lack of BP control as a function of cognitive and mood assessment scores. We used both, age-stratified (SBP < 150 mmHg) and unified (SBP/DBP < 140/90 mmHg) definitions of BP control. Results: Mean (SD) age of 384 (70.1% women) patients was 83.1 (3.1) years. Cognitive impairments were observed in 13.2% and mood disturbances in 45.5%. Mean SBP/DBP were 143.2(16.3)/83.9(9.6) mmHg. According to age-stratified and unified definition of proper BP control, goal BP were achieved in 65.4% and 38.5% of patients, respectively. More than 2/3 of patients were prescribed 3 or more antihypertensive medications. Sixty-nine % of the group adhered to antihypertensive medications, the rest having reported various degree of noncompliance that was associated with geriatric deficits. When unified goal was applied, there was a 17% higher risk of finding lack of BP control per one score lost in AMTS scale (p = 0.02). In a corresponding analysis, there was a 7% greater risk of finding lack of BP control per one-score increment in GDS test, however the trend was borderline insignificant (p = 0.06). Both trends lost statistical significance when stratified definition of BP goal was used. Conclusions: The observation, that the subclinical worsening of cognition and mood assessed with the screening tools are related to poorer BP control, lends support to the wide-spread use of the Comprehensive Geriatric Assessment even in apparently self-dependent oldest patients with hypertension.